2023
DOI: 10.1071/ah23166
|View full text |Cite
|
Sign up to set email alerts
|

Emerging health and social policy considerations for safe and quality end-of-life care in Australia – the evidence, gaps and challenges

Deb Rawlings,
Raechel Damarell,
Paul Tait
et al.

Abstract: Recognition of the importance of end-of-life care will enable improvements in the quality of care delivered to patients and their families. Australia is experiencing an increasing number of deaths, (many expected), with an aging population who are living longer, often with multimorbidity. This makes end of life care a priority. The last year of someone’s life takes place in a complex healthcare system, with increasing pressures on care delivery, placing the spotlight on health service providers to ensure that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Public health, aged care, acute care, primary care and families and relationships must work together to seamlessly support those who are dying and their families. 49 This also speaks to the difference between care as a technical provision and care and caring in the familial context.…”
Section: Discussionmentioning
confidence: 99%
“…Public health, aged care, acute care, primary care and families and relationships must work together to seamlessly support those who are dying and their families. 49 This also speaks to the difference between care as a technical provision and care and caring in the familial context.…”
Section: Discussionmentioning
confidence: 99%
“…12 Enhancing the quality of end-of-life care is a key priority to ensure that the provision of care is consistent with the unique needs of both patients and their families. 13 The quality of healthcare that patients receive at the end of life is critical to reducing distress and grief associated with the reality of approaching death for both the patient and their family or caregivers, [14][15][16] maximising patient autonomy in decision-making, 17 preserving patient dignity, [18][19][20] and ensuring a patient's level of comfort. 21 However, several studies have reported a broad range of unmet needs among patients receiving end-of-life care services that impact their quality of care, such as inadequate communication regarding expectations for end-oflife care, 22,23 poor coordination of services contributing to delayed diagnosis and treatment, 24 and a lack of emotional support.…”
Section: Introductionmentioning
confidence: 99%